Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.